Changes in lowland paddy soil fertility in the Philippines after 50 years of the Green Revolution. Issue 4 (4th July 2021) - Nakao, Atsushi; Masai, Fukiko; Timbas, Nicola; Medina, Simplicio; Abe, Susumu Shin; Tanaka, Sota; Yanai, Junta
ABSTRACT: The Green Revolution (GR) made a major contribution to increasing the rice yield in the Philippines from 1.3 t ha −1 in 1966 to 4.0 t ha −1 in 2018, but the changes in paddy soil fertility that occurred during this 50-year period remain unknown. We collected 37 soil samples from the plow layers of paddy fields in Luzon, Leyte, Panay, and Mindanao in the Philippines in 2016 and 2017 (the '2010s') and compared their fertility-related soil properties with published data for soil samples collected from the same or nearby sampling sites in 1969 (the '1960s'). Paddy soils in the Philippines had relatively high exchangeable calcium (Ca) and magnesium (Mg) content, cation exchange capacity (CEC), available silicon (Si) content, and total carbon (C) and nitrogen (N) content, reflecting their indigenous pedological background. We found that the 2010s soils had a lower available N content, particularly in wetter regions, despite the high input of N fertilizers, whereas the available phosphorus (P) showed a six-fold increase from the 1960s to the 2010s. The total potassium (K) content had significantly decreased during this period, possibly due to the mining effect of intensive farming with K-deficient fertilization. The 2010s soils contained a greater silt content and higher proportion of smectite in the clay fraction, which may have been transported from upstream via irrigation water. The increase in smectite corresponded with a significant increase in the cation exchange capacity, despite the organic C and clay contents tending to decrease, and these increases in smectite and soil pH may have contributed to the increase in the available fraction of Si that had not been applied as fertilizers. These findings demonstrate that paddy soil fertility in the Philippines changed in many ways over this 50-year period, largely owing to the direct impact of GR implementation in paddy fields but also potentially due to offsite effects from upland fields. The environmental impact of the nutrient loss and soil organic matter degradation behind the fertility improvement should be assessed holistically for the sustainable development of rice paddy ecosystems. (337 words)